Acute performance fatigability following continuous versus intermittent cycling protocols is not proportional to total work done - MacDougall, K. B.; Zhang, J.; Grunau, M.; Anklovitch, E.; MacIntosh, B. R.; MacInnis, M. J.; Aboodarda, S. J. (Applied Physiology, Nutrition, and Metabolism, 2024)
Classical training theory postulates that performance fatigability following a training session should be proportional to the total work done (TWD); however, this notion has been questioned. This study investigated indices of performance and perceived fatigability after primary sessions of high-intensity interval training (HIIT) and constant work rate (CWR) cycling, each followed by a cycling time-to-task failure (TTF) bout. On separate days, 16 participants completed an incremental cycling test, and, in a randomized order, (i) a TTF trial at 80% of peak power output (PPO), (ii) an HIIT session, and (iii) a CWR session, both of which were immediately followed by a TTF trial at 80% PPO. Central and peripheral aspects of performance fatigability were measured using interpolated twitch technique, and perceptual measures were assessed prior to and following the HIIT and CWR trials, and again following the TTF trial. Despite TWD being less following HIIT (P = 0.029), subsequent TTF trial was an average of 125 s shorter following HIIT versus CWR (P < 0.001), and this was accompanied by greater impairments in voluntary and electrically evoked forces (P < 0.001), as well as exacerbated perceptual measures (P < 0.001); however, there were no differences in any fatigue measure following the TTF trial (P = 0.149). There were strong correlations between the decline in TTF and indices of peripheral (r = 0.70) and perceived fatigability (r = 0.80) measured at the end of HIIT and CWR. These results underscore the dissociation between TWD and performance fatigability and highlight the importance of peripheral components of fatigability in limiting endurance performance during high-intensity cycling exercise.